Illegal ivory trade as transnational organized crime? an empirical study into ivory traders in Uganda - Titeca, Kristof (The British journal of criminology, 2019)
This article examines illegal ivory trade in Uganda, which constitutes a major transport route through which ivory exits Africa. The analysis is based on empirical data collected among illegal ivory traders between 2012 and 2017. The findings unpack the notion of illegal ivory trade as ‘transnational organized crime’, by showing its reliance on local and regional connections, in which ‘nodes’ are crucial. These nodes can be both traders (such as middlemen), and locations (such as border towns), connecting these various levels. In doing so, it shows how this trade functions in a decentralized and loose fashion. There are clear power differences between the traders, which is explained through the kind of connections with government officials.